Abiotic stress in marchantia polymorpha : transcriptome data generation and morphology under combinatorial stress - Lim, Peng Ken (Nanyang Technological University, 2021)
The study of abiotic stress responses in plants is complex as responses can vary across different stress combinations and plant species. However, this complexity has yet to be sufficiently addressed as intense research has only focused on single-stress responses in some model plants. Due to its genomic similarity to the ancient land plant, the common liverwort (Marchantia polymorpha) has been postulated to have an ancient set of stress responses of which stress responses in higher plants derive from. Therefore, an understanding of the stress responses in M. polymorpha can provide insights into the stress responses of higher plants. In this project, the morphology of M. polymorpha under different abiotic stress combinations (heat, cold, light, dark, salt, osmotic and nitrogen deficiency stress) have been documented and analysed to identify interesting interactions between different stress combinations. While different stress combinations largely resulted in expected morphologies, possible antagonistic interactions were observed in cold-light and heat-light stress while cold-dark stress exhibits possible synergistic interactions. Finally, analysis of gene expression data from previous single-stress and diurnal experiments of M. polymorpha suggests that additional data is required for the identification of functionally enriched gene clusters through agglomerative hierarchical clustering.